The Politics of Science Communication in Indonesia: Understanding the Role of Science Academies - Chabibah, Uswatul; Putri, Nur Rafiza; Rakhmani, Inaya; Burhanudin, Muhamad; Adiningtyas, Wahyu (UI Scholars Hub, 2024)
The role of Indonesian academies as science communicators evolves together with changing government regimes. Globally, science academies are typically not-for-profit, independent academic communities committed to providing advice for the nation in matters pertaining to science and technology. In Indonesia, science academies are historically formed under state regimes. This article, drawing on Niilo Kauppi’s framework, examines five years of science communication by the Indonesian Academy of Sciences, and two organizations under its auspices: the Indonesian Young Academy of Sciences and the Indonesian Science Fund. It reflects on their efforts to bridge the gaps between science, policy, and the public. Within the academy’s network, at times members relinguish their scientific identities to occupy the space between government and public — which in certain contexts might become disadvantageous. This is especially so in conditions where unequal power is held between the State and scientists, where the mobilization of resources, relationships, and symbols of sciences — staples for science communication —becomes ineffective.